TECHNICAL ANALYSIS OF ADDING HOLES TO THE SKEG OF A TUGBOAT AND ITS EFFECTS ON FLOW AND RESISTANCE USING THE COMPUTATIONAL FLUID DYNAMICS METHOD - David Prayogo; Abdul Rohman; Jangka Rulianto; Khairul Muzaka; I Gusti Ngurah Bagus Catrawedarma (Politeknik Negeri Batam, 2025)
Tugboats play a crucial role in supporting the safety and operational efficiency of ports and offshore activities. One of the key components in tugboat design is the skeg, which serves to enhance directional stability and reduce yawing effects. This study aims to analyze the influence of the number of holes in the skeg on the flow characteristics and resistance of a tugboat. Three skeg variations were tested: a skeg without holes, a skeg with two holes, and a skeg with four holes, under two speed conditions, namely 10 knots and 15 knots. The observed parameters include wetted surface area, drag force, and longitudinal flow velocity (velocity u). The simulation results indicate that the skeg without holes produced the lowest drag values, at 22.570 N at 10 knots and 138.430 N at 15 knots, along with a more stable and streamlined flow pattern. In contrast, adding holes to the skeg resulted in increased drag and flow disturbances in the form of vortices and fluid separation. Therefore, the skeg without holes is considered more hydro dynamically optimal for improving the operational efficiency of tugboats.